MENINGKATKAN HASIL BELAJAR IPA PADA MATERI PERUBAHAN KENAMPAKAN BUMI DAN LANGIT DENGAN MENGGUNAKAN MEDIA GAMBAR MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD PADA SISWA KELAS IV S - surianis surianis (STKIP ROKANIA, 2018)
This action research generally aims to improve science learning outcomes of students in State Elementary School 028 Rambah through the application of cooperative method of STAD type in the first semester on the subject of change of appearance of earth and sky objects. The data in this study were collected using tests, student observation sheets, teacher observation sheets, and field notes. The type of research is classroom action research. The research procedure consists of planning, execution, observation and reflection. The result of the research revealed that the value obtained by students from the cycle of cycle has increased, so that it is very suitable applied in the class in cycle I is 69,23% (good), while cycle II is 96,15% (very good). Based on the research, it can be concluded that cooperative learning model of STAD type can improve student learning outcomes.